PENGARUH KETERLIBATAN PEMBINA, KEMAMPUAN PENGURUS DAN PARTISIPASI ANGGOTA TERHADAP KINERJA KEUANGAN KOPERASI PONDOK PESANTREN - Rusdarti, - (Semarang State University, 2009)
This research to analyze influence of counselor involvement, management capability and themembers participation on financial performance of the Kopontren the simultaneously and partially. Thisresearch was carried out using survey method and taking the primary and secondary data. Survey wascarried to 12 Kopontren as a sample research, counselor respondent is 12,36 management capabilityand the members participation was secondary data. The analysis method was using path analysis.The result of research give evidence that:1. Counselor involvement, management capability and the members participation were influencedsimultaneously positive and significant on financial performance of the Kopontren have 77,70%.Financial performance was measure from liquidity, solvability and rentability to have average309,38%.2. The partially influence counselor involvement on financial performance have 34,21%. The influenceof management capability on financial performance have 18,88%. The influence of membersparticipation on financial performance have 53,90%. The independent variables are influencepositive and significant.There for suggest that attention counselor for improvement welfare to management capability for addincentive have to motivation in the work and good time expend for develop kopontren. Hoped candevelop syariah cooperative in the Moslem boarding school.Keywords: Counselor Involvement, Management Capability, Participation, Financial Performance.